Learning Quantifier Materials with Plotagon Story and Kinemaster Applications - Aenun Khayatun; Chairil Tri Suryana; Nina Nurjaman; Winda Widyaningrum (JEdu: Journal of English Education, 2021)
Learning is an important element to involve students as active learners. Learning is related to the science and technology development curriculum. Teaching contains two elements, namely teaching methods and teaching media. These two aspects are interrelated. The choice of one particular teaching method will affect the type of appropriate teaching media. This study aims to describe the use of the kinemaster application and plotagon story. This greatly affects the student learning process. By learning quantifier material with the kinemaster and plotagon story applications, it makes it easier for students to learn and increases students' interest in learning the material to be studied and makes the learning process more interesting for students. The method used in this research uses qualitative research. The data collection method is by using a questionnaire to obtain validation and responses to the questionnaire product. Where 94% feel they understand the quantifier material learning video with the kinemaster application and plotagon story. 92% find the video interesting to watch. 82% of them the video can help learn quantifier material. 74% of them do not feel bored with learning videos using kinemaster and plotagon story.